Ototoxicity and Its Early Diagnosis in Patients Receiving Cancer Chemotherapy - A Prospective Clinical Study - Gleamine Selvam Paulraj; Prem Shankar Kumar; Pankaj Kumar Sahu; Rahul Sood; Rashmi Natraj (Bengal Journal of Otolaryngology and Head Neck Surgery, 2025)
Structured Abstract Introduction: Antineoplastic drugs play an important role in the treatment of cancer at different levels & are the most cited ototoxic agents. The main objective of the study is early detection of ototoxicity in individuals receiving chemotherapy as an attempt to reduce the challenge in diagnosis and management of ototoxicity.